Thusong Service Centre and service delivery in Botlokwa Village, Limpopo Province - Motlatla, Lesetja Jack (My University, 2016)
The emergence of democracy is South Africa which lead to the inauguration of African National Congress in power in 1994, came as panacea to unlock service delivery backlogs left by the apartheid government. In order to address service delivery backlogs, government had to find effective methods that could be used to offer different government services and information in one central point. Thusong Service Centre was then adopted as an alternative solution and these Centres were rolled out across the country including Botlokwa Village in Limpopo province. Therefore the purpose of this study was to examine Botlokwa Thusong Centre to determine if the centre was able to respond to service delivery challenges affecting the communities of Botlokwa. Literature review in this study, revealed that the provision of effective service delivery requires a government’s capability to offer different government services in one central point, and Thusong Service Centre were envisaged to provide such capability. Literature review further suggests that though Thusong Service Centres are able to carry the responsibility of addressing address service delivery role they should be properly managed and financed, and should create job opportunities to the community they serve. These postulations by literature is contrary to the situation in Botlokwa Thusong Service Centre as the findings provides a different picture. The findings derived from the questionnaires which were distributed to the users of the centre revealed that Botlokwa Thusong Service Centre is not properly managed, does not receive any financial support from Limpopo Provincial government, and the Centre is unable to create jobs opportunities for the community of Botlokwa Community. Secondly, due to restrictions imposed on the Centre Manager by the Tribal Authority Office, the Centre Manager could not be interviewed instead a representative from the Tribal Authority Office was interviewed as a person having knowledge of how the Centre came into being. The representative from the Tribal authority revealed that the Botlokwa Thusong Service Centre was able to bring service delivery such as the Department of Home affairs which is able to enable Botlokwa Community to apply identity documents; Eskom from which Botlokwa Community is able to purchase electricity; South African Police Service to assist the Botlokwa Community with services such as certifying of their documents and writing affidavits. Although the Centre is trying to improve the lives of the people by making the above services available, the Centre is V unable to create job opportunities due to lack of financial support from government and private sector but the representative from the tribal authority confirmed that they will continue to engage government and private sector in this regard. The recommendations made by the study, among others, are that Botlokwa Thusong Service Centre should capacitate their employees including the centre manager be entrusted with the responsibility to engage any person without involving the office of the tribal authority. It is important that Botlokwa Thusong Service Centres should endeavour to find alternative sources of finance to help it create job opportunities to sustain itself.
Thesis (MPA.) -- University of Limpopo, 2016
Keywords: Democracy in South Africa; African National Congress; Service Delivery; Thusong Service Centre; Botlokwa Village; Public administration -- South Africa -- Limpopo Province; Municipal services -- South Africa -- Limpopo Province; Public utilities -- South Africa -- Limpopo